EPIZOOTIC SITUATION AS TO CATTLE HELMINTHIASES ON THE FARMS OF SUMY REGION - Nagorna, L. V. (Scientific Progress & Innovations, 2020)
Helminthiases were and are still unresolved problem on livestock farms of different production capaci- ties. Cattle, regardless of the natural-climatic characteristics of farm location, are affected differently by different types of helminthes. The way of handling, the number of anthelmintic treatments, and the stock den- sity influence the species characteristic of helminthiases. In case of association helminthiases development, the economic losses because of infestation increase. Accordingly, the knowledge of their nosological profile is the first step in developing effective helminthic diseases’ prevention schemes. The purpose of our work was to find out the spreading of cattle helminthiases on farms of different production capacities in Sumy region. To achieve this goal, the analysis of the statistical reporting of Sumy Regional State Laboratory of the State Service of Ukraine for Food Safety and Consumer Protection during the period from 2014 to2019 on the dy- namics of sample receiving for coprological examination and identification of positive ones was conducted. According to the results of the conducted researches, the dynamics of cattle infestation caused by helminthes on the farms in Sumy region was established. It was determined that fasciolosis, dictyocaulosis and strongy- loidosis dominated in the nosological profile of diseases. During the period of 2017–2019, no cestode infes- tation of cattle was identified. On the whole, positive dynamics of improving epizootic situation regarding cattle infestation by trematodes and nematodes was noted. Among the nematodes, during 2014–2019 the causal agents of the following helminthic diseases were identified: trichostrongylidoses, neoascarosis, dyc- tyocaulosis, bunostomosis, esophagostomosis, and strongyloidosis. The nosological profile of trematodoses was represented by the causative agents of the following diseases: fasciolosis, dicroceliosis, and paramphis- tomatidoses. There was a consistent tendency to reducing the infestation of animals with fasciolae. Among the examined livestock, the tendency was registered as to reducing the infestation with different types of hel- minthes, which is partly related to decreasing the number of livestock on farms and implementing effective schemes of helminthiases prevention.